Getting the most from your life sciences advertising agency: how can doctors be influenced? - Gowers, Barry (Henry Stewart Talks, 2009)
Why do we need creativity, How do doctors as healthcare professionals react to medical advertising?, Prescribers are specifiers, so how do they learn to trust their medicines?, How do agency creatives build desire within tight regulatory guidelines?, What do you need to optimize creativity?
Archived at 2021/02/25